Association of sleep quality with insulin resistance in obese or overweight subjects - Sima Hashemipour; Azam Ghorbani; Atoosa Khashayar; Hamideh Olfati (Sleep Science)
Introduction: Obesity or overweight are two factors associated with insulin resistance (IR). There are limited studies with regard to the role of some non-traditional factors such as sleep quality in level of IR in obese individuals. The current study aimed at investigating the association of sleep quality with IR in overweight or obese people. Material and Methods: In this cross-sectional study, 612 obese or overweight participants of the Qazvin metabolic disease study (QMDS) were evaluated. Sleep quality was measured using the Pittsburgh sleep quality index (PSQI) and compared between two groups of participants with and without IR. Results: Our findings showed that the total score of sleep quality in the IR group was significantly lower than that in the non-insulin resistant group (8.78±2.78 vs. 8.13±2.70, p=0.008). After adjustment, each unit increase of the sleep latency and subjective sleep quality scores was associated with a 1.23 and 1.33 times increased risk of IR, respectively (p<0.05).Conclusion: In the obese or overweight people, sleep quality is associated with IR.